Identifikasi Pengobatan Yang Tidak Tepat (Innapropiate Medication ) Pada Pasien Geriatri Berdasarkan American Geriatric Society (AGS) Beers Criteria 2023 - Anastasya Dian Nurratri; CitraYuliyanda Pardilawati (CV. Jasa Sukses Abadi, 2023)
Inappropriate prescribing (IP) for parents may be interpreted as a situation where pharmacotherapy is not within accepted medical standards. This includes overprescribing, misprescribing, and underprescribing which have the potential to have risks of use that outweigh the clinical benefits. The population over 60 is growing faster than any other age group as the increase in life expectancy has outpaced the decrease in the birth rate. According to world demographics, the population aged over 60 years has tripled in 50 years, from 600 million in 2000 to more than 2 billion in 2050. The number of elderly people in Indonesia is among the top 5 in the world, namely 18.1 million in 2010 and will double to 36 million in 2025. Then from 2000 to 2025, the life expectancy of Indonesia's population will reach 67.8% and increase to 73.6%. The elderly are vulnerable to various physical disorders caused by natural factors and disease factors. The aging process occurs due to changes in various organs including the gastrointestinal system, urinary system, central nervous system and others